A GENDER INEQUALITY IN MOSQUE: An-Ethnographic Approach in Kudus, Central Java - Rosyid, Moh; Kushidayati, Lina (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2023)
The mosque is a center of worship and a learning medium for Muslims. As a place of worship, according to the syariah there is no specific classification that mosques can only be dominated by one gender only. However, male dominance over the mosque as a religious public sphere occurred in the Baitussalam Kauman Mosque, Jekulo, Kudus, Central Java, Indonesia from 1923 until now. Therefore, this article seeks to analyze the factors of discrimination against females in using the mosque as a place of worship and other religious activities. Using an ethnographic approach, this article argues that discrimination against females has occurred since 1923. This happened at the same time as the establishment of the Pesantren Al-Qaumaniyah Islamic (only for male santri) and was followed by other pesantren around the mosque. The gender inequality discrimination argument relies on an unwritten rule that ideally females only pray in congregation at home. Furthermore, it is as if females are positioned as “trouble makers” because they are seen as disturbing the male congregation who are focusing on memorizing the al-Qur’an at the Baitussalam Mosque. This stereotype and discriminatory regulation is still perpetuated today under the pretext of respecting the old rules of the founders.